A cross sectional study on mothers’ insight of feeding babies with cleft lip and palate in Hyderabad city, Telangana - Turlapati, Sravya; Reddy, Parthasarathi; Polasani, Prathibha; Hameed, Irram Abbas; Mocherla, Monica; Goje, Vidyasagar (International Journal Of Community Medicine And Public Health, 2020)
Background: Feeding infants with cleft lip and palate is one of the most challenging and worrying events in a mother’s life. When the baby fails to thrive, the mother becomes anxious as the effort goes futile which may inhibit maternal bonding with the child leading to other consequences. Hence, our aim was to assess the attitudes of mothers towards feeding their babies with cleft lip and palate. Methods: A cross sectional study was conducted among mothers of children with cleft lip and palate at a cleft center in Hyderabad city. The mothers were interviewed using a self-administered questionnaire on a 3-point Likert scale. The collected data were subjected to statistical analysis using SPSS version 22. Results: A total of 96 mothers participated in the study. Among them a majority of them bottle fed their baby (85%). Escape of milk through nostrils was reported to be the most common problem faced by the child (30%). The attitudes of mothers were categorized into good (29%), moderate (62.5%) and poor (28%). Also there was a significant difference between the educational qualification, household income and clinical diagnosis with the attitude of mothers. Conclusions: In the present study, a majority of them had moderate attitude. Personal and professional care and support are the key factors influencing the mothers’ attitude.